Divergence and convergence in international regulatory policies regarding genome-edited food: How to find a middle ground - Tachikawa, Masashi; Matsuo, Makiko (Frontiers in Plant Science, 2023)
Regulations for organisms and products to which genome-editing technologies are applied are increasing in diversity, with the path-dependent effect of previous regulations for genetically modified organisms. Regulations for genome-editing technologies are a patchwork of international regulations that are difficult to harmonize. However, if the approaches are arranged in chronological order and the overall trend is examined, the regulation of genome-edited organisms and GM food products has recently been trending toward a middle ground which can be characterized as “limited convergence.” There is a trend toward the adoption of two approaches: one that considers GMOs but tries to apply simplified regulations and another that excludes them from the scope of regulations as non-GMOs but requires confirmation. In this paper, we discuss why there is a tendency toward convergence of these two approaches and examine the challenges and implications of these two approaches for the governance of the agricultural and food sectors.